1992
DOI: 10.1111/j.1699-0463.1992.tb04041.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of detection speed and yield in agitated and non‐agitated aerobic blood culture bottles

Abstract: Arpi, M. & Olesen Larsen, S. Comparison of detection speed and yield in agitated and non-agitated aerobic blood culture bottles. APMIS 100: 1061-1065, 1992.The influence of agitation on detection speed and yield was evaluated in 7,033 paired, identical aerobic blood culture bottles (Media Department, Statens Seruminstitut, Copenhagen, Denmark). One bottle was agitated and the other was incubated stationary. Of a total of 943 organisms isolated in aerobic blood culture bottles, 74% were clinically significant. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…In our opinion the current data confirm that a beta-lactam-aminoglycoside combination is a valid first choice for patients in our region suspected of bacteraemia, in accordance with a previous survey covering 1978-1983 (9). Antistaphylococcal coverage by e.g.…”
Section: Discussionsupporting
confidence: 92%
“…In our opinion the current data confirm that a beta-lactam-aminoglycoside combination is a valid first choice for patients in our region suspected of bacteraemia, in accordance with a previous survey covering 1978-1983 (9). Antistaphylococcal coverage by e.g.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, it is commonplace to find that the caregivers can’t afford to pay for blood cultures before commencement of antibiotics. The use of manual culture techniques which accounted for 89% of techniques used in this review may have greatly hampered detection of GBS and other pathogens for the following reasons: automated blood culture systems support the growth of a wider range of organisms and at lower inoculum than manual systems, they also have antibiotic removal devices such as resins which help to enhance microbial growth in the presence of antibiotics, the continuous agitation of bottles by the equipment also encourages bacterial growth [ 55 , 56 ]. Dagnew et al reported higher isolation of GBS with automated systems[ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Blood culture automates agitate the blood cultures continuously during incubation, which has been shown to increase recovery of pathogens, probably due to increased oxygenation. [42][43][44][45][46] Moreover, temperature in automated incubators is presumably more stable than that in a conventional incubator, which has to be opened in its entirety each time a bottle is added or removed.…”
Section: Discussionmentioning
confidence: 99%